Solar Cell Berkapasitas 100 Wp Menggunakan Inverter 1000 Watt - Felycia Felycia; Adi Nugraha; Sayid Bahri Sriwijaya (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2022)
Solar energy is a renewable energy source that is abundantly availabe in Indonesia.  One way to untilize solar energy is to convert it into electrical energy using photovotaic modules or solar panel called solar power plants (PLTS).  The construction of solar power plants can accelerate the electrification ratio and reduce fossil materials.  In this research, it will make a 100 Wp solar cell will be used by using a 1000 watt inverter by testing the place at the Cilegon City from 08:00 – 17:00 WIB.   Making PLTS is done by identifying components – components such as:  solar panel, DC wattmeter, SCC ( Solar Charge Controller), batteries, 1 phase MCB, and AC wattmeter.  At this PLTS the maximum power produced is 47,87 watts at 13:00 WIB.  And the minimum power produced 31,90 watts at 17:00 WIB.  It can be concluded that this PLTS can be used to help remote areas that have not yet been energized.Keywords: Solar energy, Solar Cell 100 Wp